Insights into the Inhibitory Mechanism of Viniferifuran on Xanthine Oxidase by Multiple Spectroscopic Techniques and Molecular Docking - Yaxin Yang; Qian Chen; Shiyang Ruan; Junli Ao; Shang-Gao Liao (Molecules, 2022)
Viniferifuran was investigated for its potential to inhibit the activity of xanthine oxidase (XO), a key enzyme catalyzing xanthine to uric acid. An enzyme kinetics analysis showed that viniferifuran possessed a strong inhibition on XO in a typical anti-competitive manner with an IC50 value of 12.32 μM (IC50 for the first-line clinical drug allopurinol: 29.72 μM). FT-IR and CD data analyses showed that viniferifuran could induce a conformational change of XO with a decrease in the α-helix and increases in the β-sheet, β-turn, and random coil structures. A molecular docking analysis revealed that viniferifuran bound to the amino acid residues located within the activity cavity of XO by a strong hydrophobic interaction (for Ser1214, Val1011, Phe914, Phe1009, Leu1014, and Phe649) and hydrogen bonding (for Asn768, Ser876, and Tyr735). These findings suggested that viniferifuran might be a promising XO inhibitor with a favorable mechanism of action.